2020
DOI: 10.1038/s41598-020-71386-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical implications of germline predisposition gene mutations in patients with acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is one of the most common types of leukemia. With the recent advances in sequencing technology and the growing body of knowledge on the genetics of AML, there is increasing concern about cancer predisposing germline mutations as well as somatic mutations. As familial cases sharing germline mutations are constantly reported, germline predisposition gene mutations in patients with AML are gaining attention. We performed genomic sequencing of Korean patients diagnosed with AML to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…We excluded 77 publications, including 41 animal studies, 20 about irrelevant subjects, 13 reviews, and three in languages other than English and Chinese. The remaining 30 were next given full-text reviews and all were considered eligible for this study, including nine case series, 12 , 14 21 11 case reports, 22 – 32 four reports about DDX41 -related solid cancers, 33 – 36 and six rare case reports 37 42 ( Figure 1 ). No extra study was identified from the references listed in the relevant reviews and the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 77 publications, including 41 animal studies, 20 about irrelevant subjects, 13 reviews, and three in languages other than English and Chinese. The remaining 30 were next given full-text reviews and all were considered eligible for this study, including nine case series, 12 , 14 21 11 case reports, 22 – 32 four reports about DDX41 -related solid cancers, 33 – 36 and six rare case reports 37 42 ( Figure 1 ). No extra study was identified from the references listed in the relevant reviews and the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…These pathways may be explored in future for the various anticancer therapies. Bloom syndrome patients, develop haematologic malignancies frequently [54,55]. The yeast-two hybrid assay, coimmunoprecipitation and far western analysis con rmed the C-terminal region of blm to interact directly with mlh1 to maintain genomic stability [56].…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, discerning how these mechanisms occur is also of fundamental importance to develop strategies to predict and prevent disease progression. Indeed, some mutations, particularly in the genes involved in DNA repair ( FANC genes), telomere biology disorder ( CTC1 , RTEL1 , WRAP53 ), germline myeloid neoplasm-associated genes ( DDX41 , RUNX1 ) and others such as C/EBPA and WT1 , are associated with a predisposition to an earlier onset of AML and cases of familial AML [ 42 , 43 , 44 ]. One of the most interesting ways to apply clonal evolution studies and high throughput technologies to the clinic is represented by the future perspective to be able to investigate AML response to different treatments, in particular by analyzing those clones emerging after therapy, which are often involved in relapse.…”
Section: Identifying Genetic Heterogeneity and Subclones Populations Exploiting High Throughput Techniquesmentioning
confidence: 99%